괭생이 모자반 추출물의 비장세포 면역활성 증강 효과 - 김동섭(Dong-Sub Kim); 성낙윤(Nak-Yun Sung); 한인준(In-Jun Han); 이병수(Byung-Soo Lee); 박상윤(Sang-Yun Park); 노은영(Eun Young Nho); 엄지(Ji Eom); 김건(Geon Kim); 김경아(Kyung-Ah Kim) (Journal of nutrition and health, 2019)
Purpose: This study examined the immunological activity and optimized the mixture conditions of Sargassum horneri (S. horneri) extracts in vitro and in vivo models. Methods: S. horneri was extracted using three different methods: hot water extraction (HWE), 50% ethanol extraction (EE), and supercritical fluid extraction (SFE). Splenocyte proliferation and cytokine production (Interleukin-2 and Interferon-γ) were measured using a WST-1 assay and enzyme-linked immunosorbent assay, respectively. The levels of nitric oxide and T cell activation production were measured using a Griess assay and flow cytometry, respectively. The natural killer (NK) cell activity was determined using an EZ-LDH kit. Results: Among the three different types of extracts, HWE showed the highest levels of splenocyte proliferation and cytokine production in vitro. In the animal model, three different types of extracts were administrated for 14 days (once/day) at 50 and 100 mg/kg body weight. HWE and SFE showed a high level of splenocyte proliferation and cytokine production in the with and without mitogen-treated groups, whereas EE administration did not induce the splenocyte activation. When RAW264.7 macrophage cells were treated with different mixtures (HWE with 5, 10, 15, 20% of SFE) to determine the optimal mixture ratio of HWE and SFE, the levels of nitric oxide and cytokine production increased strongly in the HWE with 5% and 10% of SFE containing group. In the animal model, HWE with 5% and 10% of SFE mixture administration increased the levels of splenocyte proliferation, cytokine production, and activated CD4+ cell population significantly, with the highest level observed in the HWE with 5% of SFE group. Moreover, the NK cell activity was increased significantly in the HWE with 5% of SFE mixture-treated group compared to the control group. Conclusion: The optimal mixture condition of S. horneri with immune-enhancing activity is the HWE with 5% of SFE mixture. These results confirmed that the extracts of S. horneri and its mixtures are potential candidate materials for immune enhancement. 본 연구는 괭생이 모자반 추출물의 추출방법에 따른 면역증강활성에 관하여 비교 관찰하였고, 추출물간의 혼합비율을 다르게 혼합하여 제조한 괭생이 모자반 추출물의 최적 면역활성을 갖는 혼합비를 평가하였다. 비장세포에 괭생이 모자반 열수 (HWE), 주정 (EE), 초임계 (SFE) 추출물을 각각 처리하였을 때 HWE 및 SFE 처리구에서 비장세포 증식능 및 사이토카인 (IL-2, IFN-γ) 분비능이 높게 나타나는 것으로 관찰되었고, 각각의 추출물을 50, 100 mg/kg BW의 농도로 2주간 마우스에 투여하고 비장을 적출하여 비장세포 활성능에 관하여 관찰한 결과, HWE 및 SFE 투여구에서 비장세포 증식능 및 사이토카인 분비능이 높게 나타나는 것으로 관찰되었다. 동물실험에서 높은 활성을 보인 HWE와 SFE의 추출물의 혼합 최적비를 평가하기 위하여 HWE에 SFE를 5, 10, 15 및 20%로 혼합하여 대식세포에 처리하여 NO 및 사이토카인 분비능에 관하여 관찰한 결과, SFE를 5%, 10% 혼합한 추출물 처리구에서 활성이 높게 나타나는 것으로 관찰되었으며 혼합추출물을 100 mg/kg BW으로 14일간 투여한 마우스의 비장세포 활성에 관하여 관찰한 결과, SFE를 5%의 비율로 혼합한 추출물 처리구 비장세포 활성이 높게 나타나는 것으로 관찰되어 HWE와 SFE의 최적 혼합 비율을 HWE에 SFE를 5% 첨가하는 것으로 결정하였다. 결정된 최적혼합비로 100 mg/kg BW의 농도로 14일간 투여한 마우스의 비장세포에서 NK 세포를 분리하여 NK 세포의 활성능을 평가한 결과, 대조구 대비 높게 증가하는 것으로 나타났다. 따라서 괭생이 모자반 추출물을 최적비율로 혼합하여 제조한 혼합추출물은 비장세포, 대식세포 및 NK 세포에 대한 높은 활성능을 나타내어 면역증진에 기여하는 것으로 판단된다.